Report of the Committee on Proposal Evaluation for Allocation of Supercomputing Time for the Study of Molecular Dynamics: Fourth Round - National Research Council (The National Academies Press, 2013)
This letter report evaluates proposals for allocation of time to the non-commercial research community on Anton, a supercomputer specially designed and built by D.E. Shaw Research (DESRES) that allows for dramatically increased molecular dynamics simulations compared to other currently available resources. Over the past three years (October 1, 2010 00e220ac201c September 30, 2013), DESRES has made available to the non-commercial research community node-hours on an Anton system housed at the Pittsburgh Supercomputing Center (PSC), based on the advice of previous National Research Council committees convened in 2010, 2011, and 2012.